Left Ventricular Untwisting in Athlete’s Heart: Key Role in Early Diastolic Filling? - Kovács, A.; Apor, A.; Nagy, A.; Vágó, H.; Tóth, A.; Nagy, A. I.; Kováts, T.; Sax, B.; Széplaki, G.; Becker, D.; Merkely, B. (International Journal of Sports Medicine, 2014)
Untwisting contributes to left ventricular filling through suction generation. We sought to investigate diastolic function and untwisting dynamics in different forms of left ventricular hypertrophy: in athlete’s heart and hypertrophic cardiomyopathy. Elite athletes in kayaking, canoeing and rowing (n=28), patients with hypertrophic cardiomyopathy (HCM, n=15) and healthy sedentary volunteers (n=13) were compared. Left ventricular volumes, wall thickness-to-volume ratio were assessed by cardiac MRI. Following conventional and tissue Doppler measurements, untwist and untwist rate were determined by speckle tracking echocardiography. Wall thickness-to-volume ratio describing remodelling was significantly higher in HCM, but similar in athletes and controls (athlete vs. HCM vs. control: 0.107±0.019 vs. 0.271±0.091 vs. 0.104±0.012 mm×m²/ml, mean±SD, p<0.001). Mitral lateral annulus e’ velocity referred to diastolic dysfunction in HCM (15.3±3.6 vs. 7.9±3.3 vs. 15.0±3.0 cm/s, p<0.01). At time point of mitral valve opening, untwist and untwist rate were significantly different: the highest values were measured in athletes, while the lowest were found in HCM (untwist: 51.3±19.1 vs. 11.6±10.4 vs. 35.9±16.3%; untwist rate: −32.5±13.0 vs. −10.6±10.8 vs. −23.0±7.7°/s, p<0.05). Untwisting correlated with E/A, e’ and E/e’. Athlete’s heart is characterized by increased untwist and untwist rate, which can aid diastolic function. Evaluation of untwisting dynamics may help to distinguish pathological hypertrophy.
Keywords: echocardiography; speckle tracking; untwist; MRI; athlete's heart